Knockdown of NEAT1 prevents post-stroke lipid droplet agglomeration in microglia by regulating autophagy - Pan, Yongli; Xin, Wenqiang; Wei, Wei; Tatenhorst, Lars; Graf, Irina; Popa-Wagner, Aurel; Gerner, Stefan T.; Huber, Sabine E.; Kılıç, Ertuğrul; Hermann, Dirk M.; Bähr, Mathias; Huttner, Hagen B.; et al. (Springer Science and Business Media Deutschland GmbH, 2024)
Background: Lipid droplets (LD), lipid-storing organelles containing neutral lipids like glycerolipids and cholesterol, are increasingly accepted as hallmarks of inflammation. The nuclear paraspeckle assembly transcript 1 (NEAT1), a long non-coding RNA with over 200 nucleotides, exerts an indispensable impact on regulating both LD agglomeration and autophagy in multiple neurological disorders. However, knowledge as to how NEAT1 modulates the formation of LD and associated signaling pathways is limited. Methods: In this study, primary microglia were isolated from newborn mice and exposed to oxygen-glucose-deprivation/reoxygenation (OGD/R). To further explore NEAT1-dependent mechanisms, an antisense oligonucleotide (ASO) was adopted to silence NEAT1 under in vitro conditions. Studying NEAT1-dependent interactions with regard to autophagy and LD agglomeration under hypoxic conditions, the inhibitor and activator of autophagy 3-methyladenine (3-MA) and rapamycin (RAPA) were used, respectively. In a preclinical stroke model, mice received intraventricular injections of ASO NEAT1 or control vectors in order to yield NEAT1 knockdown. Analysis of readout parameters included qRT-PCR, immunofluorescence, western blot assays, and behavioral tests. Results: Microglia exposed to OGD/R displayed a temporal pattern of NEAT1 expression, peaking at four hours of hypoxia followed by six hours of reoxygenation. After effectively silencing NEAT1, LD formation and autophagy-related proteins were significantly repressed in hypoxic microglia. Stimulating autophagy in ASO NEAT1 microglia under OGD/R conditions by means of RAPA reversed the downregulation of LD agglomeration and perilipin 2 (PLIN2) expression. On the contrary, application of 3-MA promoted repression of both LD agglomeration and expression of the LD-associated protein PLIN2. Under in vivo conditions, NEAT1 was significantly increased in mice at 24 h post-stroke. Knockdown of NEAT1 significantly alleviated LD agglomeration and inhibited autophagy, resulting in improved cerebral perfusion, reduced brain injury and increased neurological recovery. Conclusion: NEAT1 is a key player of LD agglomeration and autophagy stimulation, and NEAT1 knockdown provides a promising therapeutic value against stroke. Graphical abstract: [Figure not available: see fulltext.].
Keywords: Autophagy; Lipid Droplets; Microglia; NEAT1; Stroke